Der einsame Weg, Band 2 : Historisch-kritische Ausgabe - Schnitzler, Arthur (De Gruyter, 2024)
The 15th volume of the “Historical-Critical Edition of Arthur Schnitzler’s Early Works” – edited by Konstanze Fliedl since 2010 – presents Schnitzler’s play “Der einsame Weg” (1904). The entire extensive corpus of material is genetically reconstructed; the manuscripts are reproduced as facsimiles and provided with diplomatic transcriptions. Furthermore, the volume includes a reading text with a critical apparatus, detailed descriptions of the genesis and the printing history based on additional sources and testimonies, and a commentary. Volume 1: https://e-book.fwf.ac.at/o:1980 Volume 2: https://e-book.fwf.ac.at/o:1981 Der 15. Band der – von Konstanze Fliedl seit 2010 herausgegebenen – historisch-kritischen Ausgabe von Arthur Schnitzlers Frühwerk präsentiert Schnitzlers dreiaktiges Schauspiel „Der einsame Weg“ (1904). Das gesamte umfangreiche Material wird genetisch rekonstruiert, Handschriften werden faksimiliert und mit diplomatischer Umschrift versehen. Der Band bietet zudem einen Lesetext mit Variantenapparat, detaillierte Ausführungen zur komplexen Entstehungs-, und Druckgeschichte anhand weiterer Quellen und Zeugnisse und einen Kommentar. Band 1: https://e-book.fwf.ac.at/o:1980 Band 2: https://e-book.fwf.ac.at/o:1981